1974
DOI: 10.1002/jsfa.2740251212
|View full text |Cite
|
Sign up to set email alerts
|

Formation of dimethyl sulphide from S‐methylmethionine in onion seedlings (Allium cepa)

Abstract: Homogenates of onion seedlings catalyse the decomposition of S-methylmethionine into dimethyl sulphide and homoserine. The reaction is rather slow and seems not to be of primary importance in onion flavour formation or Smethylmethionine metabolism. Extracts of scarlet runner bean seedlings are also active, whereas dormant onion bulb and other seedlings tested showed no or very low activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Our determination of DMPT was based on this presumed specificity. In contrast to DMPT, S-methylmethionine, another sulfonium compound which has been reported as the precursor of DMS in higher plants, releases DMS with aqueous alkali only at high temperatures (Hattula and Granroth 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Our determination of DMPT was based on this presumed specificity. In contrast to DMPT, S-methylmethionine, another sulfonium compound which has been reported as the precursor of DMS in higher plants, releases DMS with aqueous alkali only at high temperatures (Hattula and Granroth 1974).…”
Section: Methodsmentioning
confidence: 99%
“…They found that dimethyl sulfide production was highly correlated with S-methylmethionine sulfonium, but the role of methionine as a dimethyl sulfide precursor was not as certain. However, S-methylmethionine is easily formed from methionine in many plants (Hattula and Granroth 1974), so methionine may have at least an indirect role in the formation of dimethyl sulfide. Methionine also has a role in the formation of methanethiol, dimethyl disulfide, and dimethyl trisulfide.…”
Section: Possible Precursorsmentioning
confidence: 99%
“…Furthermore, dimethyl sulfide is released in significant amounts with other compounds as a volatile compound of paprika (Capsicum annuum) (Cremer and Eichner, 2000). It is also found in onion and garlic but it not important for the taste formation of these foods (Hattula and Granroth, 1974). Dimethyl sulfide is the most abundant sulfur compound in beer, superior to the taste threshold of 30-45 µL.…”
Section: Analysis Of Chemical Compounds By Dynamic Headspacementioning
confidence: 99%